Histopathological Study on Induced Eeffects of Cadmium on Liver, Gizzard and Kidney of Larus argentatus - Noreen Raza; Tasneem A. Saqib; Ghazala Yasmeen; Syed Naeemul Hassan Naqvi; Mijaz Hijazi (Journal of Basic & Applied Sciences, 2016)
The study was carried out on the effects of cadmium (Cd) on liver, gizzard and kidney of Larus argentatus. Significant alterations were observed after the treatment of high and low dose of cadmium chloride injected to Larus argentatus. Investigation of the effects of Cd on body tissues was done by sectioning of fixed tissue by paraffin section techniques. Major changes were noted at high dose of cadmium chloride in liver, kidney and gizzard. While, under low dose of cadmium chloride, mild to moderate changes in hepatocytes around blood vessels in liver; reduction in thickness of epithelium and muscular layer in gizzard; and slight alterations in arrangement of tubules of loop of henle in the kidney of proximal convoluted tubules with granular cytoplasm were observed. No lesions were found in the mentioned body tissues of Larus argentatus of control group.